Q1: 15 points Q2: 25 points Q3: 20 points Q4: 20 points Q5: 20 points Total: 100 points
Question text is in black, solutions in blue.
A closed formula is a rule that gives the value of the n'th number of the sequence in terms of n, rather than using other terms of the sequence.
The negation of a statement p is the statement "it is not the case that p", which is true when p is false and false when p is true.
Two compound propositions (using the same atomic variables) are logically equivalent if they have the same truth value as one another for each possible setting of the atomic variables.
In the implication "p → q", p is the premise. It is the statement which, if it is true, requires the conclusion to be true as well for the implication to be true.
The Division Theorem says that for every integer a and every positive integer b, there exist integers q and r such that a = qb + r and 0 ≤ r < b.
¬B(d) ∨ (B(c) ∧ B(m)). The parentheses are necessary.
Given any dog, if it is the same size as Duncan, then either it is barking or Mia is not barking.
S(c, m) → ∀x: [S(x, m) → ¬S(x, d)]
Either Mia is barking and is not the same size as Duncan, or it is not the
case that Cardie is barking and Duncan is the same size as Mia.
Equivalently, using DeMorgan, you could say "Either Mia is barking and
is not the same size as Duncan, or Cardie is not barking, or Duncan is not
the same size as Mia."
∃x: ∀y: (¬B(y) → S(x, y))
Since the columns representing the values of the entire
expressions (the → on the left and the ¬ on the right)
are identical, the two compound propositions are logically
equivalent.
p --> (q or not r) not(r or p or not q)
-----------------------------------------------
0 1 0 1 1 0 1 0 0 0 0 1 0
0 1 0 0 0 1 1 1 0 0 0 1 0
0 1 1 1 1 0 1 0 0 0 0 0 1
0 1 1 1 0 1 1 1 0 0 0 0 1
-----------------------------------------------
1 1 0 1 1 0 1 0 0 1 0 1 0
1 0 0 0 0 1 0 1 1 1 1 1 0
1 1 1 1 1 0 1 0 0 1 0 0 1
1 1 1 1 0 1 1 1 1 1 0 0 1
(Hint: Use the Division Theorem and consider the three cases of the possible remainder when n is divided by 3. You don't want to use induction, since you need all integers and not just positive ones.)
By the Division Theorem, n may be written as 3q + r where r equals 0, 1, or 2.
(Many of you instead used the Division Theorem on n3 - n, which
would have been ok if you had shown that the r = 1 and r = 2 cases led to
contradictions, but you didn't.)
In the case where r = 0, n3 - n equals
(3q)3 - 3q = 27q3 - 3q = 3(9q3 - q).
Since the number in parentheses is an integer, we have shown that
n3 - n is divisible by 3.
In the case where r = 1, n3 - n equals
(3q+1)3 - (3q+1) =
27q3 + 27q2 + 9q + 1 - 3q - 1 =
3(9q3 + 9q2 + 2q).
Since the number in parentheses is an integer, we have shown that
n3 - n is divisible by 3.
In the case where r = 2, n3 - n equals
(3q+2)3 - (3q+2) =
27q3 + 54q2 + 36q + 8 - 3q - 2 =
3(9q3 + 18q2 + 11q + 2).
Since the number in parentheses is an integer, we have shown that
n3 - n is divisible by 3.
Many of you observed that n3 - n may be rewritten as
(n+1)n(n-1). This allows for an easier proof, because in the case
where r = 0 we have that n is divisible by 3, in the case where r = 1
we have that n-1 is
divisible by 3, and in the case where r = 2 we have that n+1 is divisble
by 3. So the product always contains a factor divisible by 3, and thus
is itself divisible by 3.
Our statement P(n) is "an = (n3 - n)/3".
For our base case, we must prove P(1). The number a1 is
defined to be 0, and (13 - 1)/3 is also 0, so P(1) is true.
For the inductive case, we assume that an-1 =
((n-1)3 - (n-1))/3 and use the rule that an =
an-1 + n(n-1). This tells us that an is equal to
(n3 - 3n2 + 3n - 1 - n + 1)/3 + n(n-1) =
(n3 - 3n2 + 2n + 3n2 - 3n)/3 =
(n3 - n)/3
The algebra simplifies somewhat if you keep a common factor of n-1 in all
the terms. In any event, we have assumed P(n-1) and proved P(n), which
completes the inductive case.
Last modified 19 October 2016